Fifty Shades of Brexit: Britain's EU Referendum and its Implications for Europe and Britain. Issue 1 (2nd January 2017) - Oliver, Tim
Abstract: Britain's vote to leave the EU has raised more questions than answers, which is ironic given that David Cameron's aim for the referendum was to settle the European question in British politics. The outcome, which reflected a range of causes, leaves significant uncertainties overhanging UK politics, UK-EU relations and wider European politics. It is likely that the confused outcome of the referendum and the technicalities of Brexit mean that for both the UK and the EU future relations will resemble fifty shades of grey rather than some black and white division of in or out.